Arugula production as a function of irrigation depths and potassium fertilization - Elis M. de Freitas; Luan B. Giovanelli; Fábio T. Delazari; Márcio L. dos Santos; Silvio B. Pereira; Derly J. H. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Arugula is a vegetable that has gained more highlight in the consumption, being rich in potassium, sulfur, iron, omega-3 and vitamins A and C. Availability of water and nutrients are limiting factors for production of this crop. In this context, the objective of this study was to evaluate the production of arugula subjected to different irrigation depths and potassium fertilization. The experiment was conduct between August and September 2015. The experimental design was completely randomized in split-plot scheme. Irrigation depths L1, L2, L3 and L4 (25, 50, 75 and 100% of crop evapotranspiration, respectively) represented the plots and potassium doses K1 and K2 (200 and 400 kg ha-1, respectively) represented the subplots. Although the highest yield was obtained with highest irrigation depth and highest potassium dose, it is recommended the cultivation of arugula with the lowest irrigation depth and the lowest potassium dose, considering the higher value of water use efficiency for this treatment.